Paradoxical Engagement: How Outsourcing Shapes Organizational Identity in Digital Public Spheres - Prasetyo, Bambang Dwi; Muchtar, Moch. Shobastian Mahendra; Artanti, Neni Puji (Komunikator, 2025)
This research examines the paradox of outsourcing digital engagement in organizational communication, highlighting how third-party agencies and independent content creators influence brand identity in online public spaces. With more organizations turning to external contributors for social media management, questions arise about the consistency and authenticity of their messaging. The study aims to determine whether outsourcing boosts audience interaction while compromising alignment with organizational values. Adopting a mixed-methods design, it incorporates digital ethnography and content performance triangulation through thematic analysis, engagement metrics, and stakeholder perception surveys involving internal teams, agencies, and creators. Results show that while outsourced content generates greater engagement, it is often viewed by internal teams as lacking authenticity and deviating from core values. This indicates a tension between creative impact and brand consistency, underlining the need for deliberate, strategic collaboration. Organizational identity in digital platforms is thus portrayed as fluid and negotiated, offering insights for managing co-created content across evolving communication landscapes